A molecular docking and dynamic approach to screen inhibitors against ZnuA1 of Candidatus Liberibacter asiaticus. Issue 6 (13th April 2021) - Saini, Gunjan; Dalal, Vikram; Gupta, Deena Nath; Sharma, Nidhi; Kumar, Pravindra; Sharma, Ashwani Kumar
ABSTRACT: Huanglongbing is the most destructive disease of citrus worldwide caused by Candidatus Liberibacter asiaticus (CLas). Present control and management could not remove the huanglongbing disease. ZnuA1 is the periplasmic component of ZnuABC transporter system, involved in Zn metal ion uptake in CLas. The current study focuses on targeting the CLas ZnuA1 for the identification of potent molecules. Therefore, structure-based virtual screening was done against CLas ZnuA1, and the binding energies were evaluated using molecular docking. Potential lead molecules were selected based on binding potentials, interactions with active site residues of proteins, and pharmacophore properties. Molecular dynamics simulation and MMPBSA result confirmed that identified molecules (ZINC15670529, ZINC92774705, ZINC06510089, ZINC79841324, and ZINC69594834) bound at the active site of CLas ZnuA1 and result in the formation of highly stable CLas ZnuA1-inhibitor(s) complex as compared to CLas ZnuA1-RDS51. The study reported that identified molecules appeared to be the suitable novel putative inhibitors of CLas ZnuA1 and can be useful for further design of new derivatives with higher potency and specificity.